PWE-074 Variation in The Management of Barrett's High Grade Dysplasia in England. (17th August 2016) - Chadwick, G; Cromwell, D; ,
Abstract : Introduction: The British Society of Gastroenterology recommend that patients with Barrett's high grade dysplasia (HGD) are considered for active treatment, with endoscopic therapy considered the treatment of choice. 1 We sought to investigate patterns of treatment among patients with newly diagnosed HGD in England. Methods: This study used data collected for the National Oesophago-Gastric Audit (NOGCA) on patients diagnosed with HGD in England between 1 st April 2012 and 31 st March 2015. The study looked at the relationship between patient's initial treatment, and their characteristics and diagnostic process. We also examined patterns of treatment by strategic clinical network (SCN) where the patient was diagnosed. We estimated case-mix adjusted rates of surveillance using logistic regression models. Results: There were 1, 284 patients diagnosed with HGD over 3 years. Mean (SD) age at diagnosis was 71.1 (±10.6) years; 74.1% were men. 795 (65.7%) were managed endoscopically, 66 (5.4%) had an oesophagectomy, and 350 (28.9%) underwent surveillance alone. The proportion of patients managed by surveillance increased with age (p < 0.001), but was not affected by a history of comorbidities (p = 0.981). Patients were more likely to receive active treatment if they were referred from a Barrett's surveillance program (84.9% vs 59.4%, p < 0.001), or if they had the diagnosis confirmed either by a second pathologist (79.1% vs 57.2%, p < 0.001), or repeat biopsy (78.1% vs 62.1%, p < 0.001). Active treatment was also more common if patients were discussed at a MDT meeting (75.1% vs 53.6%, p < 0.001). After adjusting for age, sex, and history of comorbidities, we observed significant variation across SCNs in the proportion of patients managed by surveillance alone (Figure 1 ), ranging from 4% to 54%. Conclusion: A substantial proportion of patients with HGD are managed by surveillance alone. Trusts should review their management of these patients, and consider referring cases to specialist centres for treatment. Reference: 1 Fitzgerald RC, et al . BSG guidelines on the diagnosis and management of Barrett's oesophagus. Gut 2014;63 (1):7–42. Disclosure of Interest: None Declared